Puer-et-senex na comunicação mercadológica: um estudo nos processos de criação de marca - Valione Junior, Miguel (2013)
This dissertation aims at investigating the manifestations of imaginary in marketing communication processes. Specifically, it seeks to ascertain how the images of the eternal child and the wise old man (Puer and Senex) are presented in the media discourse. Relations were established between these images and communication processes associated with the creation and development of brands. For discussion of the images of Puer and Senex we reviewed the studies developed by Jung, von Franz and Hillman. The corpus consists of three advertising campaigns for companies of different fields, whose brands are recognized in the media discourse and the global imaginary: (1) Chanel; (2) Ray-Ban; and (3) Apple. The theoretical basis interweaves concepts from various areas of knowledge, particularly of media studies (Jenkins); communication, culture, image, imaginary (Durand, Maffesoli and Leão); creation processes in the media (Salles and Leão); advertising (Carrascoza and Covaleski); and analytical and archetypal psychology (Jung, von Franz and Hillman). To achieve the proposed objectives, the research is organized in three steps: (1) literature review; (2) implementation of three case studies (descriptive, interpretive and relational); and (3) analysis and interpretation of the corpus according to the creation method proposed by Leão. Analyzes have identified the presence of Puer and Senex as constituent elements of the marketing discourse and noted the importance of the imaginary media in the construction of brand identity